2019
DOI: 10.1186/s12938-019-0654-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale experimental study on the effects of different weight-bearing levels during moderate treadmill exercise on bone quality in growing female rats

Abstract: BackgroundBone tissue displays a hierarchical organization. Mechanical environments influence bone mass and structure. This study aimed to explore the effects of different mechanical stimuli on growing bone properties at macro–micro–nano scales.MethodsSixty five-week-old female Wistar rats were treadmill exercised at moderate intensity with the speed of 12 m/min, and then randomly divided into five groups according to weight-bearing level. After 8 weeks of experiment, femurs were harvested to perform multiscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Previous studies have shown different results on whether treadmill running can reduce TRACP concentration. A study on the treadmill running in rats also found that rats increased bone formation after 8 weeks of running without affecting bone resorption [19]. This is consistent with our current conclusion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown different results on whether treadmill running can reduce TRACP concentration. A study on the treadmill running in rats also found that rats increased bone formation after 8 weeks of running without affecting bone resorption [19]. This is consistent with our current conclusion.…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, findings obtained from 5-month-old male SD rats may not be applicable to female rats. A recent study showed that loading of a 1-month-old female rat with a weight-bearing and moderate-intensity treadmill can promote bone formation and improve trabecular microstructure [19]. Future work will include the effects of treadmill exercise with different intensities on bone quality of female SD rats with the same age to obtain more comprehensive results and conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise had a signi cant impact on bone histomorphology, and exercise could increase BMD and improve the related indicators of bone tissue microstructure (Fang et al, 2019;Troy et al, 2018). In this study, there were no signi cant differences between the TC and TY group.…”
Section: Exercise Improved the Bone Histomorphology Of The T2dm Micementioning
confidence: 48%
“…To generate a more intense exercise and/or load, the principle of weight bearing was applied on the vertebrae of animals. A backpack, representing up to 20% of body weight of the animal tested, was used during the whole running session [ 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Effects Of Physical Exercises On Bone Health Statusmentioning
confidence: 99%